Optimalisasi Pengelolaan Arsip melalui Sistem Informasi Kearsipan Digital (SIKENDI) di Fakultas Ekonomi dan Bisnis Universitas Padjadjaran - Putri, Salsa Amalia (Universitas Negeri Padang, 2023)
This study aims to determine the process of digital archive management at the Faculty of Economics and Business, Universitas Padjadjaran through the Sikendi website-based application. This research was also conducted to find out the background of Sikendi's creation, obstacles in its use, and changes that occur in manual archive management with digital management. The method used was descriptive qualitative with data collection techniques including observation, interviews, literature review, and documentation. The data was then analyzed using the Miles and Huberman data analysis model. The research informants were 2 archivists at the Faculty of Economics and Business, Padjadjaran University. The results showed that archive digitization makes management more efficient and effective. The digital system used, Sikendi, consists of 5 stages, namely creation, categorization, filing, classification coding, and digital media transfer. The obstacles encountered in managing with a digital system are in the aspects of lack of human resources, lack of facilities, and systems that experience errors.